2022
DOI: 10.1021/acssynbio.2c00130
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Biology Toolbox, Including a Single-Plasmid CRISPR-Cas9 System to Biologically Engineer the Electrogenic, Metal-Resistant Bacterium Cupriavidus metallidurans CH34

Abstract: Cupriavidus metallidurans CH34 exhibits extraordinary metabolic versatility, including chemolithoautotrophic growth; degradation of BTEX (benzene, toluene, ethylbenzene, xylene); high resistance to numerous metals; biomineralization of gold, platinum, silver, and uranium; and accumulation of polyhydroxybutyrate (PHB). These qualities make it a valuable host for biotechnological applications such as bioremediation, bioprocessing, and the generation of bioelectricity in microbial fuel cells (MFCs). However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…It was found that the induced resistance was mediated by copper oxidase CopA, which was reduced to Au(0) nanoparticles in the periplasm by the intermediate detoxification Au complex. , This is a biological way for bacteria to detoxify metal ions and an unnatural process of biomineralization. Second, there are studies on the complex structure of biosynthetic DNA–gold in Escherichia coli and Staphylococcus, which has fluorescence effect and is used for the bioresponsive fluorescence imaging of bacteria. , Different bacteria were used to explore the biosynthesis of gold nanoparticles, revealing that different bacterial biosynthetic pathways are inconsistent, leading to differences in efficiency and gold nanostructures. …”
Section: Biosynthesis Systemsmentioning
confidence: 99%
“…It was found that the induced resistance was mediated by copper oxidase CopA, which was reduced to Au(0) nanoparticles in the periplasm by the intermediate detoxification Au complex. , This is a biological way for bacteria to detoxify metal ions and an unnatural process of biomineralization. Second, there are studies on the complex structure of biosynthetic DNA–gold in Escherichia coli and Staphylococcus, which has fluorescence effect and is used for the bioresponsive fluorescence imaging of bacteria. , Different bacteria were used to explore the biosynthesis of gold nanoparticles, revealing that different bacterial biosynthetic pathways are inconsistent, leading to differences in efficiency and gold nanostructures. …”
Section: Biosynthesis Systemsmentioning
confidence: 99%
“…Genetic manipulation is essential not only for elucidating the biological functions of bacterial genes, but also for effectively employing bacteria in synthetic biology applications encompassing industrial, environmental, and biomedical fields. CRISPR-Cas-based technologies have remarkably enhanced the efficiency of correlating genotype and phenotype [3][4][5] , and constructed advantageous bacteria for synthetic biology applications [6][7][8][9] . However, these techniques exhibit efficient performance in E. coli and some closely related enterobacteria, while functioning inefficiently in other bacterial species.…”
Section: Introductionmentioning
confidence: 99%